2011
DOI: 10.1016/j.cplett.2011.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the PAni morphology deposited on the carbon fiber: An analysis of the capacitive behavior of this hybrid composite

Abstract: a b s t r a c t CF/PAni composites were synthesized using the polymerization chemistry. Three different deposition times were used in the synthesis, such as: 30, 60 and 90 min. The morphology and the structure of composites were analyzed by SEM and Raman spectroscopy, respectively. The influence of the mass of polymer deposited on the carbon fiber, with respect to the values of specific capacitance (C sp ) was analyzed by electrochemical experiments. The optimum value of the C sp was obtained for CF/PAni-30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…The evolution of the specific capacitance observed in this work is in agreement with the results reported earlier by other researchers [12,16,21,23,62]. It has been generally shown that the capacitance is enhanced by either smooth homogeneous PAni coatings of small thickness [12] or nanofiber-shaped assemblies with a certain degree of 3D order and small diameter [22,23] obtained at low PAni loading densities. Such thin nanostructures are believed to provide fast access of electrolyte and shortened path lengths for ion and electron transport.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The evolution of the specific capacitance observed in this work is in agreement with the results reported earlier by other researchers [12,16,21,23,62]. It has been generally shown that the capacitance is enhanced by either smooth homogeneous PAni coatings of small thickness [12] or nanofiber-shaped assemblies with a certain degree of 3D order and small diameter [22,23] obtained at low PAni loading densities. Such thin nanostructures are believed to provide fast access of electrolyte and shortened path lengths for ion and electron transport.…”
Section: Discussionsupporting
confidence: 91%
“…Three-dimensional networks of nanofibrilar or nanowire structures seem the most frequently encountered morphology for PAni deposited on high surface area carbon substrates (e.g., carbon fibers or cloths), either by electrochemical [20,21,62,63] or conventional in-situ chemical polymerization [22,23,24]. However, in agreement with our results, some authors have obtained smooth dense layers [8,63] or a transition from this morphology to irregular or randomly connected nanofibrilar aggregates upon extending the polymerization time [12,62]. It has also been reported that long reaction time [23] or prolonged galvanostatic oxidation [20] lead to incontrollable growth among carbon fibers and result in a detrimental effect via peeling-off from the carbon surface.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations